Incentivizing sustainable rangeland practices and policies in Colombia’s Orinoco region (2019)
Livestock grazing, along with agriculture, are key drivers of deforestation and land degradation that subsequently affect ecosystem service provision in the tropics. Although environmental and agricultural policies may curtail these negative effects, information is needed on how specific programs and instruments could be used to incentivize ranchers into adopting rangeland practices to achieve land conservation. We examine what encourages livestock ranchers to adopt more sustainable rangeland practices with various technical and conservation attributes in Colombia’s Orinoco region. First, we analyze a management alternative based on an improved pasture (IP) approach traditionally used in tropical South America, and another practice that promotes silvopastoral systems (SP) that better sustain the long term provision of ecosystem services. Second, we assess the influence that technical assistance and conservation payment instruments can have on the adoption of the IP or SP programs.